2012
DOI: 10.1186/1479-5876-10-189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-dose intravenous vitamin C on inflammation in cancer patients

Abstract: BackgroundAn inflammatory component is present in the microenvironment of most neoplastic tissues. Inflammation and elevated C-reactive protein (CRP) are associated with poor prognosis and decreased survival in many types of cancer.Vitamin C has been suggested as having both a preventative and therapeutic role in a number of pathologies when administered at much higher-than-recommended dietary allowance levels.Since in vitro studies demonstrated inhibition of pro-inflammatory pathways by millimolar concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 72 publications
5
124
0
5
Order By: Relevance
“…Previously, a significant decrease in CA 15.3 was observed following immunotherapy for breast cancer (45). Furthermore, the correlation between CA 15.3 and CRP has been documented in different types of cancer patients after the inhibition of pro-inflammatory pathways by vitamin C (46). To the best of our knowledge, this is the first study demonstrating such a correlation in breast cancer.…”
Section: Discussionsupporting
confidence: 47%
“…Previously, a significant decrease in CA 15.3 was observed following immunotherapy for breast cancer (45). Furthermore, the correlation between CA 15.3 and CRP has been documented in different types of cancer patients after the inhibition of pro-inflammatory pathways by vitamin C (46). To the best of our knowledge, this is the first study demonstrating such a correlation in breast cancer.…”
Section: Discussionsupporting
confidence: 47%
“…Vitamin C is a potent antioxidative agent, it influences mitochondrial function by decreasing the generation of reactive oxygen species (ROS) through stimulation of the activity of superoxide dismutase and glutathione peroxidase and alteration of the activity of the electron transport chain [16]. Vitamin C also has anti-inflammatory properties [17]. Some data indicate that, in rodents, dietary supplementation with vitamin C could prevent fat deposition induced by a HF diet.…”
Section: Prace Oryginalnementioning
confidence: 99%
“…IVC therapy reduced CRP levels and decreased plasma concentrations of several inflammatory and angiogenic cytokines; moreover, these decreases correlated with reductions in the levels of tumor markers [15,30]. Prostate cancer may be a particularly promising candidate for IVC therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms were proposed such as the effects of high doses of vitamin C on angiogenesis, suppression of inflammation, modulation of gene expression, and improvement of immune cells' functioning [13][14][15][16]. There are in vitro and animal studies that showed that high-dose vitamin C induces pro-oxidant effects and selectively kills cancer cells [17,18].…”
Section: Introductionmentioning
confidence: 99%